Health ramifications of smart devices - LaPlaca, D. A.; Turner, H. (Strength and Conditioning Journal, 2020)
Smart devices, such as smartphones, smartwatches, and tablets, have rapidly become more popular in the fitness industry and provide a variety of benefits ranging from tracking barbell velocity to displaying online training programs. These devices use cellular data and Wi-Fi to transmit information, which have shown to potentially pose risks to our health. The purpose of this article is to both (a) provide the reader with researched information on how the use of smart devices may pose a risk to our health and (b) provide practical applications for how to reduce the health risks from using these devices. For a video abstract of this article, see Supplemental Digital Content 1, http://links.lww.com/SCJ/A274.